Myocarditis in SARS-CoV-2 infection vs. COVID-19 vaccination: A systematic review and meta-analysis - Navya Voleti; Surya Prakash Reddy; Paddy Ssentongo; Paddy Ssentongo (Frontiers in Cardiovascular Medicine, 2022)
BackgroundThis study aimed to compare the incidence of myocarditis in COVID-19 vaccines and in severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) infection groups.MethodsElectronic databases (MEDLINE, Scopus, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and the WHO Global Literature on Coronavirus Disease) and trial registries were searched up to May 2022, for randomized controlled trials and observational cohort studies reporting the risk of myocarditis associated with the COVID-19 vaccines and the risk associated with SARS-CoV-2 infection. We estimated the effect of COVID-19 infection and vaccines on rates of myocarditis by random-effects meta-analyses using the generic inverse variance method. Meta-regression analyses were conducted to assess the effect of sex and age on the incidence of myocarditis.ResultsWe identified 22 eligible studies consisting of 55.5 million vaccinated cohorts and 2.5 million in the infection cohort. The median age was 49 years (interquartile range (IQR): 38–56), and 49% (IQR: 43 to 52%) were men. Of patients diagnosed with myocarditis (in both vaccination and COVID-19 cohort) 1.07% were hospitalized and 0.015% died. The relative risk (RR) for myocarditis was more than seven times higher in the infection group than in the vaccination group [RR: 15 (95% CI: 11.09–19.81, infection group] and RR: 2 (95% CI: 1.44-2.65, vaccine group). Of patients who developed myocarditis after receiving the vaccine or having the infection, 61% (IQR: 39–87%) were men. Meta-regression analysis indicated that men and younger populations had a higher risk of myocarditis. A slow decline in the rates of myocarditis was observed as a function of time from vaccination. The risk of bias was low.ConclusionIn this systematic review and meta-analysis, we found that the risk of myocarditis is more than seven fold higher in persons who were infected with the SARS-CoV-2 than in those who received the vaccine. These findings support the continued use of mRNA COVID-19 vaccines among all eligible persons per CDC and WHO recommendations.